Purification, biochemical characterization and antifungal activity of a new lipid transfer protein (LTP) from Coffea canephora seeds with α-amylase inhibitor properties - Zottich, Umberto (2011)
Background: A growing number of cysteine-rich antimicrobial peptides (AMPs) have been isolated from plants and particularly from seeds. It has become increasingly clear that these peptides, which include lipid transfer proteins (LTPs), play an important role in the protection of plants against microbial infection. Methods: Peptides from Coffea canephora seeds were extracted in Tris–HCl buffer (pH 8.0), and chromatographic purification of LTP was performed by DEAE and reverse-phase HPLC. The purified peptide was submitted to amino acid sequence, antimicrobial activity and mammalian α-amylase inhibitory analyses. Results: The purified peptide of 9 kDa had homology to LTPs isolated from different plants. Bidimensional electrophoresis of the 9 kDa band showed the presence of two isoforms with pIs of 8.0 and 8.5. Cc-LTP 1 exhibited strong antifungal activity, against Candida albicans, and also promoted morphological changes including the formation of pseudohyphae on Candida tropicalis, as revealed by electron micrograph. Our results show that Cc-LTP 1 interfered in a dose-dependent manner with glucose-stimulated, H + -ATPase- dependent acidification of yeast medium and that the peptide permeabilized yeast plasma membranes to the dye SYTOX green, as verified by fluorescence microscopy. Interestingly, we also showed for the first time that the well characterized LTP 1 family, represented here by Cc-LTP 1 , was also able to inhibit mammalian α-amylase activity in vitro. Conclusions and general significance: In this work we purified, characterized and evaluated the in vitro effect on yeast of a new peptide from coffee, named Cc-LPT1, which we also showed, for the first time, the ability to inhibit mammalian α-amylase activity.